2020
DOI: 10.1038/s41598-020-69155-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of megaplasmids encoding the type VI secretion system in Campylobacter jejuni isolated from chicken livers and gizzards

Abstract: Megaplasmids in Campylobacter spp. likely play important roles in antibiotic resistance, virulence, and horizontal gene transfer. In this study, megaplasmids pCJDM202 (119 kb) and pCJDM67L (116 kb) from C. jejuni strains WP2-202 and OD2-67, respectively, were sequenced and characterized. These megaplasmids contained genes for tetracycline resistance [tet(O)], the Type IV secretion system, conjugative transfer and the Type VI secretion system (T6SS). The T6SS genes in Campylobacter plasmids encoded genes and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
(88 reference statements)
1
26
0
Order By: Relevance
“…Interestingly, several C. jejuni megaplasmids also carry T6SS genes (Gunther et al, 2016;Fakhr, 2016, 2017). Most recently, megaplasmids pCJDM202 and pCJDM67L from C. jejuni WP2-202 and OD2-67 strains, respectively, were found to harbour the T6SS cluster, along with the tetracycline resistance gene tetO, and T4SS conjugative DNA transfer systems (Marasini et al, 2020). The authors demonstrated that the presence of the T6SS on the megaplasmids contributed to enhanced haemolysis, suggested to support the survival of C. jejuni in retail meats (Marasini et al, 2020).…”
Section: T6ss-containing Campylobacter Jejuni Integrated Element 3 Represents a Novel Pathogenicity Island Variantmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several C. jejuni megaplasmids also carry T6SS genes (Gunther et al, 2016;Fakhr, 2016, 2017). Most recently, megaplasmids pCJDM202 and pCJDM67L from C. jejuni WP2-202 and OD2-67 strains, respectively, were found to harbour the T6SS cluster, along with the tetracycline resistance gene tetO, and T4SS conjugative DNA transfer systems (Marasini et al, 2020). The authors demonstrated that the presence of the T6SS on the megaplasmids contributed to enhanced haemolysis, suggested to support the survival of C. jejuni in retail meats (Marasini et al, 2020).…”
Section: T6ss-containing Campylobacter Jejuni Integrated Element 3 Represents a Novel Pathogenicity Island Variantmentioning
confidence: 99%
“…Homologues of TraG and transfer coupling protein VirD4, a component of the Agrobacterium tumefaciens Type IVa secretion system (T4SSa), have been previously identified in the chromosomes of C. jejuni 81-176 and ATCC 43431, as well as in plasmids pCC31 and pTet (Batchelor et al, 2004;Poly et al, 2005;Chandran Darbari and Waksman, 2015). T4SS DNA conjugation systems were recently found harboured on megaplasmids in C. jejuni (Grohmann et al, 2018;Marasini et al, 2020). The T6SS-positive and TraGcontaining megaplasmid pCJDM202 from C. jejuni WP2-202 strain was successfully transferred by conjugation to a T6SSnegative mutant NCTC11168 Nal + recipient cell, with the hcp gene observed in the transconjugants, thus demonstrating a role in the transfer of T6SS-containing megaplasmids to transconjugants (Marasini et al, 2020).…”
Section: Conjugative Systemsmentioning
confidence: 99%
“…The GA1 and GA2 T6SS loci are contained on Integrative and Conjugative Elements (ICE) and are present in diverse Bacteroidales species [ 3 ]. In other bacterial lineages, T6SS loci are typically contained on non-core genomic islands, but, with few exceptions [ 8 ], are rarely found on conjugative elements. Some T6SS-associated genes, such as immunity genes [ 9 ], reside on mobile elements, and a full T6SS locus is present on a mobile prophage-like element in environmental Vibrio cholerae strains [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effectors Nte1 to 5 are also encoded in the same locus, but with Nte6 encoded elsewhere on the plasmid. To date, plasmid encoded T6SS have only been described in Campylobacter species (Marasini and Fakhr, 2016), with this plasmid T6SS mobilised via conjugation (Marasini et al, 2020). Although other small plasmids have been reported in N. cinerea (Knapp et al, 1984; Roberts, 1989) and N. cinerea can be a recipient of N. gonorrhoeae plasmids (Genco et al, 1984), it is not yet known whether T6SS plasmids are widespread among Neisseria , or whether the plasmid can be mobilised by conjugation or transformation.…”
Section: Discussionmentioning
confidence: 99%